Steam Distillation of Essential Oil from Lemongrass (Cymbopogon citratus) using Microwave Pretreatment - Sri Wahyu Murni, Ir., MT; Tutik Muji Setyoningrum; Gogot Haryono (Eksergi, 2020)
Essential oils from lemongrass (Cymbopogon citratus) containing citral are very potential to be used in food and pharmacy industries. The process of isolating essential oils is still constrained by its low yield. In order to increase yield, in this research, isolation of essential oil by steam distillation method was carried out using microwave pretreatment. The results showed that pretreatment using microwave for 2 minutes had the effect of increasing yield up to 1.4 times compared to without pretreatment. The essential oil produced using microwave pretreatment had physical properties (colour, odor, density, and refractive index) similar to those without pretreatment. Composition analysis by GC-MS showed that essential oils extracted using microwave pretreatment and without pretreatment contain geranial (Ecitral or citral-a), neral (Z-citral or citral-b) and mircena as the main components.